2023
DOI: 10.1021/acsami.3c11767
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride-Tethered Membrane Lipase Sensor

Upeksha Mirissa Lankage,
Stephen A. Holt,
Samara Bridge
et al.

Abstract: Sensors that can quickly measure the lipase activity from biological samples are useful in enzyme production and medical diagnostics. However, current lipase sensors have limitations such as requiring fluorescent labels, pH control of buffer vehicles, or lengthy assay preparation. We introduce a sparsely tethered triglyceride substrate anchored off of a gold electrode for the impedance sensing of real-time lipase activity. The tethered substrate is self-assembled using a rapid solvent exchange technique and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 35 publications
2
1
0
Order By: Relevance
“…In more detail, Table 1 summarizes the full set of electrochemical parameters that were obtained by fitting the EIS data to the equivalent circuit model and confirmed that the fitted parameter values were in good agreement with expected ranges. More specifically, the fitted G m signal for the E. coli tBLM platform was around 1.36 ± 0.45 µS, which agrees well with recently studied tBLM platforms composed of biologically relevant two-chain phospholipids or three-chain triglycerides [39]. Of note, the fitted C m signal was 0.83 ± 0.17 µF/cm 2 , which is within the range reported for tBLM platforms composed exclusively of two-chain phospholipids (~1.2-1.4 µF/cm 2 ) or three-chain triglycerides (~0.6 µF/cm 2 ).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…In more detail, Table 1 summarizes the full set of electrochemical parameters that were obtained by fitting the EIS data to the equivalent circuit model and confirmed that the fitted parameter values were in good agreement with expected ranges. More specifically, the fitted G m signal for the E. coli tBLM platform was around 1.36 ± 0.45 µS, which agrees well with recently studied tBLM platforms composed of biologically relevant two-chain phospholipids or three-chain triglycerides [39]. Of note, the fitted C m signal was 0.83 ± 0.17 µF/cm 2 , which is within the range reported for tBLM platforms composed exclusively of two-chain phospholipids (~1.2-1.4 µF/cm 2 ) or three-chain triglycerides (~0.6 µF/cm 2 ).…”
Section: Resultssupporting
confidence: 88%
“…More specifically, the fitted G m signal for the E. coli tBLM platform was around 1.36 ± 0.45 μS, which agrees well with recently studied tBLM platforms composed of biologically relevant two-chain phospholipids or three-chain triglycerides [ 39 ]. Of note, the fitted C m signal was 0.83 ± 0.17 μF/cm 2 , which is within the range reported for tBLM platforms composed exclusively of two-chain phospholipids (~1.2–1.4 μF/cm 2 ) or three-chain triglycerides (~0.6 μF/cm 2 ).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations